Socialization of Pain Management in Cancer Patients: Practical Education for Patients and Families - Mawaddah; Utami, Rizka Wahyu; Weni Sulastri; Dimas Dewa Darma; Gilang Ade Setiawan; Sahmy Rahmaryza (Bengkulu Institute, 2024)
Pain is one of the most common symptoms experienced by cancer patients, which can significantly impact quality of life if not treated properly. Socialization regarding pain management is needed to increase the knowledge and skills of patients, families and health workers in treating cancer pain holistically. This community service activity was carried out at the Baiti Jannati Cancer Shelter Home with the aim of providing education about the basic concepts of pain, pain scales, as well as pharmacological and non-pharmacological techniques for pain management. The evaluation results showed that 90% of participants understood pain management and 93% of participants were able to carry out non-pharmacological technical steps. So it can be concluded that this community service activity has a positive impact on cancer patients in carrying out pain management independently.